Postmortem biochemistry: Current perspectives and the road ahead - Singh Shekhawat, Raghvendra; Meshram, Vikas; Kanchan, Tanuj (Journal of Indian Academy of Forensic Medicine, 2021)
Thanato-biochemistry or postmortem biochemistry is a comprehensive speciality study of biochemistry in which fluids and tissues retrieved from the human corpse are subjected to qualitative and quantitative estimation of desirable biochemical parameters. The field of postmortem biochemistry has started evolving in the last few decades. The conventional autopsy practice relies on the morphological findings observed during necropsy. At many occasions, the aid of pathology and forensic science laboratories is taken for histochemical examination and chemical analysis, respectively. The analysis of the biochemical parameters from the post mortem body samples can offer intensive help in assessing the derangements in the functional, biological and molecular parameters, which are not observed in the traditional method of autopsy conduction.